Top-Down Prioritization of Salient Items May Produce the So-Called Stimulus-Driven Capture - Benoni, Hanna (Frontiers in Psychology, 2018)
The current study proposes that top-down attentional prioritization of salient items may produce the so-called stimulus-driven capture. To test this proposal, the “expectation-based paradigm” was designed on the basis of a visual search task. In Experiment 1, a task-irrelevant singleton frame was presented at the same location in 70% of the trials. The target was either presented at chance level within the singleton location, or away from it. In line with the singleton capture phenomenon, participants were faster in identifying the target when it appeared in the singleton location compared to non-singleton locations. However, leaving out the singleton frame in 30% of the trials led to a similar effect; participants were faster in identifying the target when it appeared in the expected singleton location compared to expected non-singletons locations (a “quasi-capture” effect). These results suggest that the participants allocated their attention to the expected singleton location, rather than that the singleton itself captured attention. In Experiment 2, the same task-irrelevant color singleton was presented in a random position in 70% of the trials. This color frame was shown as a non-singleton in all of the 30% singleton-absent multicolored trials. A similar facilitation effect was obtained when the target appeared in the expected singleton color frame compared to other frames, in singleton-absent trials as in singleton-present trials. These results further support the idea that instances of singleton capture can be explained by top-down attentional shifts toward singleton items. Theoretical implications of these results are discussed. Mostly, the study calls to consider the possibility that all sources of attentional control may be represented by a continuous variable of top-down control, including the category of “physical salience.”